Saikosaponin D improves nonalcoholic fatty liver disease via gut microbiota-bile acid metabolism pathway - Lan Li; Shengye Yang; Xinyu Liang; Yameng Liu; Hualing Xu; Xiaozhen Guo; Cen Xie; Xiaojun Xu (Food Science and Human Wellness)
Non-alcoholic fatty liver disease (NAFLD) is the main cause of chronic liver disease worldwide. Bupleurum is widely used in the treatment of non-alcoholic fatty liver, and saikosaponin D (SSD) is one of the main active components of Bupleurum. The purpose of this study was to investigate the efficacy of SSD in the treatment of NAFLD and to explore the mechanism of SSD in the improvement of NAFLD based on “gut-liver axis”. Our results showed that SSD dose-dependently alleviated high fat diet-induced weight gain in mice, improved insulin sensitivity, and also reduced liver lipid accumulation and injury-related biomarkers aspartate aminotransferase (AST) and alanine aminotransferase (ALT). Further exploration found that SSD inhibited the mRNA expression levels of farnesoid X receptor (Fxr), small heterodimer partner (Shp), recombinant fibroblast growth factor 15 (Fgf15) and apical sodium dependent bile acid transporter (Asbt) in the intestine, suggesting that SSD improved liver lipid metabolism by inhibiting intestinal FXR signaling. SSD can significantly reduce the gut microbiota associated with bile salt hydrolase (BSH) expression, such as Clostridium. Decreased BSH expression reduced the ratio of unconjugated to conjugated bile acids, thereby inhibiting the intestinal FXR. These data demonstrated that SSD ameliorated NAFLD potentially through the gut microbiota-bile acidintestinal FXR pathway and suggested that SSD is a promising therapeutic agent for the treatment of NAFLD.